2018
DOI: 10.1101/259358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time efficient preparation methods for MRI brain scanning in awake young children and factors associated with success

Abstract: Objective. Young children are often unable to remain still for magnetic resonance imaging (MRI).Various preparation methods have been reported to avoid sedation or anesthesia, with mixed success rates and feasibility. Here we describe a time-efficient preparation method and factors associated with successful scanning in young chdilren.We recruited 134 children aged 2.0-5.0 years for an MRI study. Some children completed a training session on a mock scanner, and all children received a 15-20 minute introduction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Findings from our study corroborate previous reports that have emphasized the importance of allowing young children to desensitize to the sights, sounds, and MRI environment. While several previous studies have indicated that the introduction of mock MRI practice sessions before the experimental session may significantly reduce potential movement and data loss during MRI scanning ( Carter et al, 2010 ; de Bie et al, 2010 ; Woods-Frohlich et al, 2010 ; Barnea-Goraly et al, 2014 ; Theys et al, 2014 ; Thieba et al, 2018 ), few have examined how individual differences within pediatric populations may need to be considered when designing MRI desensitization interventions. It is essential to consider what steps researchers and clinicians can take to ensure the comfort of children and the chances of successful data collection carefully based on the needs of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study corroborate previous reports that have emphasized the importance of allowing young children to desensitize to the sights, sounds, and MRI environment. While several previous studies have indicated that the introduction of mock MRI practice sessions before the experimental session may significantly reduce potential movement and data loss during MRI scanning ( Carter et al, 2010 ; de Bie et al, 2010 ; Woods-Frohlich et al, 2010 ; Barnea-Goraly et al, 2014 ; Theys et al, 2014 ; Thieba et al, 2018 ), few have examined how individual differences within pediatric populations may need to be considered when designing MRI desensitization interventions. It is essential to consider what steps researchers and clinicians can take to ensure the comfort of children and the chances of successful data collection carefully based on the needs of the child.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to understand which behavioral characteristics, including temperament, may predict scanning success across different neurodevelopmental disorders.Findings from our study corroborate previous reports that have emphasized the importance of allowing young children to desensitize to the sights, sounds, and MRI environment. While several previous studies have indicated that the introduction of mock MRI practice sessions before the experimental session may signi cantly reduce potential movement and data loss during MRI scanning(55,(72)(73)(74)(75), few have examined how individual differences within pediatric populations may need to be considered whendesigning MRI desensitization interventions. It is essential to consider what steps researchers and clinicians can take to ensure the comfort of children and the chances of successful data collection carefully based on the needs of the child.…”
mentioning
confidence: 99%